PEMBERDAYAAN LABORATORIUM DAN SIKAP SISWA DI LABORATORIUM DALAM PEMBELAJARAN SCIENCE DI SEKOLAH MENENGAH ATAS CHARITAS JAKARTA - BAMBANG WIDJANARKO (ACADEMIA: Jurnal Inovasi Riset Akademik, 2021)
This study aims to reveal the empowerment of laboratories at Charitas High School in Jakarta. In this study, researchers will observe the completeness of laboratory facilities and infrastructure, the ability of teachers and technical laboratory management as research variables. The subjects of this study were students and teachers of Charitas High School who used the Physics, Chemistry and Biology laboratories. Data were collected through questionnaires, observations, and interviews. Data were analyzed descriptively. In the research on the completeness of laboratory facilities and infrastructure, the ability of teachers and technical laboratory management in the good category. The supervision/evaluation carried out by the teacher is in the sufficient category. The students' attitude towards learning using the laboratory was in the very good category. The determinants of learning to use the laboratory include the completeness of laboratory infrastructure, the ability of teachers and technical laboratory management. ABSTRAKPenelitian ini bertujuan untuk mengungkapkan peberdayaan laboratorium di Sekolah Menengah Atas Charitas di kota Jakarta. Dalam penelitian ini peneliti akan mengamati kelengkapan sarana dan prasarana laboratorium, kemampuan guru dan teknis pengelolaan laboratotium sebagai variabel penelitiannya. Subjek penelitian ini adalah siswa-siswa dan guru-guru Sekolah Menengah Atas Charitas yang menggunakan laboratorium Fisika, Kimia dan Biologi. Data dikumpulkan melalui angket, observasi, dan wawancara. Data dianalisis secara deskriptif. Dalam penelitian kelengkapan sarana dan prasarana laboratorium,kemampuan guru dan teknis pengelolaan laboratorium pada kategori baik. Supervisi/evaluasi yang dilakukan oleh guru pada kategori cukup. Sikap siswa terhadap pembelajaran menggunakan laboratorium pada kategori sangat baik. Faktor-faktor determinan pembelajaran menggunakan laboratorium meliputi kelengkapan sarana prasarana laboratorium, kemampuan guru dan teknis pengelolaan laboratorium.